2008
DOI: 10.1097/olq.0b013e31817fa2cc
|View full text |Cite
|
Sign up to set email alerts
|

HIV/STI Risk Behaviors Among Latino Migrant Workers in New Orleans Post-Hurricane Katrina Disaster

Abstract: Latino migrant workers in New Orleans reported risky sexual behaviors and low condom use within a potential bridge position. Although a low prevalence of CT and GC was found, there was a high percent of self-reported HIV infection. The cultural and contextual factors that place these migrant workers and their sex partner(s) at risk for HIV/STI need further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 15 publications
3
42
0
Order By: Relevance
“…We found, as have others [25], that over time there was a trend away from FSW to main partnering. Consistent with our prior work, we found that despite high levels of FSW patronage and binge drinking, migrant men had low rates of STIs [19].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…We found, as have others [25], that over time there was a trend away from FSW to main partnering. Consistent with our prior work, we found that despite high levels of FSW patronage and binge drinking, migrant men had low rates of STIs [19].…”
Section: Discussionsupporting
confidence: 85%
“…Despite these statistics, the majority of studies of Latino men have been conducted on men who have sex with men (MSM) [15], thus it is important to investigate prevalence rates among heterosexual Latinos as well. And while few prevalence studies have been conducted among Latino migrant men [14], the few studies that have done biological testing found low prevalence rates despite high rates of HIV/STI risk behavior [17][18][19].…”
Section: Latinos and Hivmentioning
confidence: 97%
See 1 more Smart Citation
“…Numerous studies also suggest that migrant men living predominantly in male settings and groups [1]- [4] [26] [27] and those who drink alcohol are substantially more likely to engage in risky behaviours such as unprotected sex [28]. Other contributing factors to HIV and syphilis vulnerability include low knowledge of HIV and syphilis transmissions and prevention [9] [10] [29], availability of cheap sex, singlehood, low perceived vulnerability to HIV and syphilis [9] [10] [28], and existing cultures of risky sexual behaviours [30]. The uptake of safer sex measures and patterns of health service in these migrant populations is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Kissinger [15] recontacted a small sample of young women who had accessed clinical reproductive health services before the storm and found that many of them had stopped using birth control, contracted sexually transmitted infections or gotten pregnant after the storm. Similarly, she found high rates of risk behaviors among a sample of Latino migrant workers who had newly arrived after the storm [16]. These results cannot demonstrate a causal relationship between Katrina and change in risk.…”
Section: Behavioral Impactmentioning
confidence: 58%